THE ROLE OF SOCIAL SERVICES IN CHILD CARE FACING THE LAW IN MAKASSAR CITY - Amelia, Sesca Ayu; Yamin, Muh Nur; Herman, Herman (Universitas Negeri Makassar, 2025)
This study aims to determine how much the Role of Social Services in Handling Children Against the Law in Makassar City. This type of research uses descriptive qualitative research with data collection techniques, namely observation, interviews, and documentation. The data obtained from the research results are then processed using case study analysis techniques with pattern matching to determine the form of the role of the Social Service in handling Children Against the Law in Makassar City. The results of this study indicate that the role of the Social Service in handling Children Against the Law in Makassar City is based on five indicators that must be achieved in providing an ethical role, namely: (1) the facilitative role has been running well with advocacy and mentoring services provided to children, (2) the educational role has also been running well in the form of strengthening, (3) the representational role is less than optimal in carrying out its role due to the lack of communication that runs between social workers and local communities related to ABH, (4) the technical role is also still not optimal due to monitoring that is not in accordance with the reality in the field, and (5) The role of social services in handling children in conflict with the law in Makassar City is still not optimal. The conclusion in this study is that there are four indicators that are congruent, namely the facilitative role, educational role, and Children Against the Law and the indicators that are not congruent are in the representational role and technical role.